6G virtualized beamforming: a novel framework for optimizing massive MIMO in 6G networks - Ahmed M. Alwakeel (EURASIP Journal on Wireless Communications and Networking)
Abstract The advent of 6G networks promises unprecedented connectivity, with massive multiple-input multiple-output (MIMO) technology playing a critical role in achieving high throughput, low latency, and enhanced spectral efficiency. However, optimizing massive MIMO for 6G present’s challenges related to beamforming efficiency, power consumption, and dynamic network environments. This paper introduces a novel framework for 6G Virtualized Beamforming that leverages virtualization techniques to enhance beam management in massive MIMO systems. Our framework employs a combination of advanced machine learning algorithms and software-defined networking to dynamically allocate beamforming resources, improving adaptability in high-density environments and optimizing signal-to-noise ratios. By virtualizing beamforming control, the proposed framework reduces the overhead of hardware dependencies and facilitates seamless integration with existing 6G infrastructure. Furthermore, the system incorporates predictive analytics for proactive beam steering and user allocation, enhancing network performance while minimizing power consumption. Simulation results show a 22% reduction in power consumption and a 19% increase in spectral efficiency compared to traditional beamforming approaches. This study provides a foundation for scalable, virtualized MIMO systems that can meet the demands of next-generation wireless communications. Our research opens avenues for further exploration into the interplay between virtualization and beamforming in 6G, with implications for the future design of more flexible, cost-effective network architectures.